Voltage regulation in a single-stage three-phase boost-inverter using modified phasor pulse width modulation method for stand-alone applications - Afiat Milani, Alireza (Kansas State University, 2013)
In this thesis, a modified version of the phasor pulse width modulation (PPWM) switching method for use in a single-stage three-phase boost inverter is presented. Because of the required narrow pulses in the PPWM method and limitations in controller resolution, e.g. dSPACE, the desired switching pattern for a boost inverter requires a costly processor. A low resolution processor can cause pulse dropping which results in some asymmetric conditions in output waveforms of the boost inverter and therefore, an increase in the THD of the output waveform. In order to solve this problem, a new switching pattern is developed which guarantees symmetric conditions in the switching pattern by discretizing the switching pattern in every switching cycle. This switching pattern has been applied to a boost inverter model developed by SimPowerSystems toolbox of MATLAB/Simulink. The model has been simulated in a wide range of input DC voltage and load. Moreover, a laboratory-scaled three-phase boost inverter has been designed, built, and tested using an identical switching pattern in the same input voltage and load range. Both simulation and experimental results confirm the effectiveness of the new switching pattern.
Keywords: Boost inverter; Phasor PWM; Electrical Engineering (0544)